The compilation of indigenous knowledge regarding insect pests in small-scale farming communities in North Eastern South Africa - Schoeman, A.S. (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Sustainable Insect Management))--University of Pretoria, 2005.